Implementasi Pembagian Laba Dan Ujrah Dalam Usaha Tekstil Serat Daun Nanas Berdasarkan Prinsip Ekonomi Syariah - Wiharja, Jana; Mutiah, Ridla; Damayanti Rusmana, Fenny (CV. ULIL ALBAB CORP, 2024)
This research aims to understand the meaning and impact of profit sharing and ujrah in the pineapple leaf fiber textile business based on sharia economic principles for capital owners, managers, and workers. Participants in this research are capital owners, managers and workers of the business who were selected purposively. The instruments of this research are in-depth interviews, participant observation, and documentation. This research data analysis uses qualitative data analysis techniques with data reduction steps, data presentation, and drawing conclusions. The results of this research show that CV Serat AL FIBERS has succeeded in applying the principles of Islamic Economics in profit distribution and Ujrah. The application of these Principles provides benefits to Pineapple farmers, capital owners and workers. CV Seratt AL FIBERS implements a 50:50 profit sharing system from the selling price between capital owners and workers. This system is based on the mudharabah principle in Islamic economics. In this system, the capital owner provides all the business capital, while the workers provide the labor and expertise. The distribution of profits and ujrah in the pineapple leaf fiber textile business based on sharia economic principles has a deep meaning for participants, namely as a form of prosperity, justice, brotherhood and obedience to Allah SWT.